Status of “Siberia-2” SR sourse preinjector - Gudkov, B.A.; Korchuganov, V.N.; Ostreiko, G.N.; Serdobintsev, G.V.; Tarnetsky, V.V.; Kazakov, S.Yu.; Ushkov, V.L.; Fetisov, A.I. (Вопросы атомной науки и техники, 1999)
Improvements made in linac systems have significantly increased the reliability of its operation. At present time the linac injects an electron beam with an energy of 75 MeV, beam current of 65 mA (DE/E=1%), with a pulse duration of 18 ns at a repetition rate of 1 pps.